The pilgrims of Rayne [compact disc, unabridged] - MacHale, D. J. (MacHale, D. J. Pendragon (Brilliance Audio (Firm)), 2007)
With Saint Dane seemingly on the verge of toppling all of the territories, Pendragon and Courtney set out to rescue Mark and find themselves traveling--and battling--their way through different worlds as they try to save all of Halla.